1993
DOI: 10.1111/j.1365-2672.1993.tb02991.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of a plant deleterious rhizosphere pseudomonad and its inhibitory metabolite(s)

Abstract: A cell‐free culture filtrate of the plant growth inhibitory bacterial isolate Å313, identified as Pseudomonas fluorescens, was tested for its effect on wheat root elongation in vitro, with and without various pretreatments. The filtrate showed a strongly inhibitory effect on root elongation and could be heated to 100°C for 5 min or incubated at a pH within the range of 4–10 without losing its activity. Unlike other root growth‐inhibitory bacterial metabolites the effect of the filtrate was not reversed by meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…It has been reported widely (4,12,15,27,31,34) that the relative importance of biotic and abiotic determinants in microbial and plant-microbe interactions in the rhizosphere can be determined more precisely in gnotobiotic systems than in the field, where heterogeneous, mostly ill-defined factors come into play. The findings of the present work, which were obtained under gnotobiotic conditions, combined with previous reports (1,2,18,20,32,35), emphasize that proper assessment of the influence of bacterial properties on the outcome of root colonization requires careful consideration of the test plant and of the indicator effects that must be taken into account. This view is supported by several lines of evidence with respect to production of siderophores and HCN.…”
supporting
confidence: 55%
“…It has been reported widely (4,12,15,27,31,34) that the relative importance of biotic and abiotic determinants in microbial and plant-microbe interactions in the rhizosphere can be determined more precisely in gnotobiotic systems than in the field, where heterogeneous, mostly ill-defined factors come into play. The findings of the present work, which were obtained under gnotobiotic conditions, combined with previous reports (1,2,18,20,32,35), emphasize that proper assessment of the influence of bacterial properties on the outcome of root colonization requires careful consideration of the test plant and of the indicator effects that must be taken into account. This view is supported by several lines of evidence with respect to production of siderophores and HCN.…”
supporting
confidence: 55%
“…[34]. Bacterial production of sufficiently high concentrations of phytohormones may explain the observed root hair deformations in our study as well as the plant growthpromoting effects observed in studies with P. putida and Azospirillum [7,29,35,36].…”
Section: Root Colonizationsupporting
confidence: 64%
“…Soil bacteria produce a wealth of metabolites, a few of which have been identiWed and characterized. An example of a plant growth inhibitory compound produced by some pseudomonads is hydrogen cyanide (Schippers et al 1990), but pseudomonads have also been found to produce other unidentiWed phytotoxins reducing root growth (Frederickson and Elliott 1985;Åström et al 1993), and production of thaxtomin A that also reduces seedling root growth (KrasnoV et al 2005) is well-known among streptomycetes. Our results suggest that the ratio between bacteria producing such inhibitory substances and bacteria producing plant root growth stimulating compounds increased with plant age.…”
Section: Discussionmentioning
confidence: 97%